Awakening in Daily Life according to the Principle of the Dependent Origination - Phrommidet, Phramaha Thongsuk (Journal of Buddhist Innovation Review, 2025)
Awareness in daily life begins with observing and understanding that thoughts, all emotions and actions are caused by causes according to the process of Dependent Origination. Knowing this makes it possible to better deal with suffering. Reduce the causes that will lead to more suffering, and choose to do more things that are beneficial. Awakening by practicing mindfulness in all activities, developing mindfulness, praying, and considering the occurrence and extinction of thoughts will make life full of wisdom and awakening at every moment. In addition, daily awakening helps to be mindful of the present. Be aware of the things around you, both in thoughts, actions, and reactions to what happens, and be able to choose to respond consciously and wisely, rather than following emotions or habits. It makes life very efficient in terms of work. Good at managing stress, relationships with others, and stress management. It can reduce suffering from various factors in everyday life.